(3TQM TeSjI GdMSGHs - (3CHi ESMGb YHO Gddgs; (3GdMSf Hf eMeO Hf GdMSjf Gdbej GdfjSGHhQqj, fXGe GdOjf, hjbGd dg GdCYQL , GdpqfnXGe,J (B850 (3g` s
(3ChdgG (B:s
(3hHYO aEfi WGdeG cfJ YGRekG Ydi Cf CcJH hQjbkG eQJHkG Ke QCjJ GdfGS Edi TeSjI GdMSGH QGZHjf s
(3BNQgG (B:s
(3JeJ gPg GdfSNI hCcedJgG Ydi SHjd GdGSJYLGd ai YTjI Gdjhe GdSGHY YTQ ef TgQ ThGd s
(3GfXQ TeSjI GdMSGH ai cTa GdXfhf L (B2 (3U (B1062s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B216 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B281s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B56 s
Keywords: (3GdQjGVjGJs